Target মাধ্যমিক 2025
\((p^2+q^2)x^2-2(pr+qs)x+(r^2+s^2)=0\) দ্বিঘাত সমীকরণের বীজদ্বয় সমান হলে প্রমাণ করাে \(ps=qr\)

যেহেতু, সমীকরণের বীজদ্বয় সমান ।
\(\therefore \) নিরূপক শূন্য ।
\(\therefore \{-2(pr+qs)\}^2-4(p^2+q^2)(r^2+s^2)=0\)
বা, \(4(p^2r^2+q^2s^2+2pqrs)\)

\(-4(p^2r^2+p^2s^2+r^2q^2+q^2s^2)=0\)



বা, \((p^2r^2+q^2s^2+2pqrs)\)

\(-(p^2r^2+p^2s^2+r^2q^2+q^2s^2)=0\)



বা, \(\cancel{p^2r^2}+\cancel{q^2s^2}+2pqrs\)

\(-\cancel{p^2r^2}-p^2s^2-r^2q^2-\cancel{q^2s^2}=0\)




বা, \(-p^2s^2-r^2q^2+2pqrs=0\)
বা, \(p^2s^2+r^2q^2-2pqrs=0\)
বা, \((ps-qr)^2=0\)
বা, \(ps-qr=0\)
বা, \(ps=qr\) (প্রমাণিত)
Ganitsarani.in